Nature of Corporate Social Responsibility and Its Importance for Working Women - Koleva–Stefanova, Desislava (Research Papers, 2020)
The article address the challenges of today's labour markets and the importance of corporate social responsibility, considered by contemporary working women and their career prospects. The article provides a brief retrospective of the development of CSR over the years and its nature. Some factors that have a negative impact on a woman's employment are listed. Based on indicators characterizing women's employment in Bulgaria, conclusions are drawn regarding the impact of Bulgarian corporate responsibility on women employed.
Keywords: Social security; Working women; Equal opportunities; Corporate social responsibility; Labour market